Familial Mediterranean Fever Complicated by a Triad of Adrenal Crisis: Amyloid Goiter and Cardiac Amyloidosis - Sadi A. Abukhalaf; Beesan W. Dandis; Tasnim Za’tari; Adham M. Amro; Tareq Z. Alzughayyar; Yazan A. Rajabi (Case Reports in Rheumatology)
Background. FMF is a common disease in the Mediterranean populations and may be complicated by AA amyloidosis. The coexistence of adrenal and thyroid amyloidosis in AA amyloidosis secondary to familial Mediterranean fever (FMF) is an extremely rare reported condition. We presented a previously unreported triad of adrenal, thyroid, and cardiac amyloidosis secondary to FMF. Presentation of Case. We reported a 23-year-old Palestinian male patient presented with hypotension, vomiting, diarrhea, and abdominal pain. The patient was subsequently diagnosed to have an adrenal crisis with both amyloid goiter and cardiac amyloidosis. Conclusion. It is crucial to recognize the adrenal crisis in patients with AA amyloidosis secondary to FMF who present similarly to acute FMF inflammatory episodes. The adrenal crisis has high morbidity and mortality, especially if not recognized early in the course of the disease.